Physical demands in Spanish male and female elite football referees during the competition: a prospective observational study - Martin-Sanchez, M. L.; Oliva-Lozano, J. M.; Garcia-Unanue, J.; Felipe, J. L.; Moreno-Pérez, V.; Gallardo, L.; Sánchez-Sánchez, J. (Science and Medicine in Football, 2022)
Objective: The aim of this study was to analyze the physical demands of elite male and female field referees in match play and compare the physical demands between male and female football referees in the competition. Methods: Match data were collected from 36 elite football referees (19 males and 17 females) during a total of 409 football matches. Electronic performance and tracking systems based on global positioning systems (GPS) were used in this research. Results: Male referees experienced significantly greater physical demands (p < 0.05) in men league than female referees in women league for total distance, explosive distance, high-intensity breaking distance, total of sprints, sprinting distance, high-speed running distance, high-speed running actions, maximal speed, total of accelerations and decelerations, maximal acceleration and deceleration, acceleration/deceleration. Conclusions: Therefore, strength and conditioning coaches should consider these gender differences in match demands to maximize the fitness-fatigue response of the referees since this may lead to a better performance during the decision-making process in the competition.